2019
DOI: 10.1007/s11665-019-04249-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Effect of Rolling on the Localized Stress and Strain Induction for Wire + Arc Additive Manufactured Structures

Abstract: Cold rolling can be used in-process or post-process to improve microstructure, mechanical properties and residual stress in directed-energy-deposition techniques, such as the high deposition rate wire + arc additive manufacturing (WAAM) process. Finite element simulations of the rolling process are employed to investigate the effect of rolling parameters, in particular rolling load and roller profile radius on the residual stress field as well as plastic strain distribution for the profiled roller. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…The creation of non-uniform mesh density does not require special techniques or algorithms and can be done using standard finite element analysis (FEA) software tools. Such a strategy to generate efficient models has been widely adopted in 2D [40,49,50] and 3D [33,34,38,[41][42][43][45][46][47] simulations of rolling and burnishing.…”
Section: Non-uniform Mesh Densitymentioning
confidence: 99%
See 4 more Smart Citations
“…The creation of non-uniform mesh density does not require special techniques or algorithms and can be done using standard finite element analysis (FEA) software tools. Such a strategy to generate efficient models has been widely adopted in 2D [40,49,50] and 3D [33,34,38,[41][42][43][45][46][47] simulations of rolling and burnishing.…”
Section: Non-uniform Mesh Densitymentioning
confidence: 99%
“…Cozzolino et al [33] used an FEM model with significantly shorter length (465 mm) compared to the actual workpiece (750 mm) that was rolled during experiments, so as to reduce computational time, and the short model predicted similar results to the full scale model. For rolling in a WAAM component, Abbaszadeh et al [34] developed a model with a length of 100 mm for a deformable component, which was rolled along the minimal length under steady state, and they found that a further increase of the rolling distance in analysis did not make any marked difference in the result. Short models have also been used in other rolling scenarios.…”
Section: Reduced Length Of Modelled Componentmentioning
confidence: 99%
See 3 more Smart Citations